1972
DOI: 10.1136/adc.47.253.396
|View full text |Cite
|
Sign up to set email alerts
|

Families of Children with Repeated Accidents

Abstract: Husband, P., and Hinton, P. E. (1972). Archives of Disease in Childhood, 47, 396. Families of children with repeated accidents. The families of 24 children who attended an accident department with repeated injuries are described. The children frequently had an extrovert type of personality and there were often associated family problems. Coexistent psychiatric or organic illness in other members of the family was common. We suggest that the family background should be investigated whenever children attend a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
2

Year Published

1985
1985
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(12 citation statements)
references
References 9 publications
1
9
0
2
Order By: Relevance
“…This is consistent with US linkage studies 5-10 and with reports based on grouped data in Western countries. [1][2][3][4] The steep gradient by maternal education is consistent with other studies [5][6][7][8][9][10] and is also in agreement with previous studies of birth weight, 13 infant mortality, 14 or child growth 15 in the Czech Republic. Maternal marital status, maternal age, and the number of previous live births (as a proxy for the number of children in a family) have all been previously found to strongly influence mortality from injuries in infants 5-8 10 and in young children.…”
Section: Consistency With Other Studiessupporting
confidence: 89%
See 1 more Smart Citation
“…This is consistent with US linkage studies 5-10 and with reports based on grouped data in Western countries. [1][2][3][4] The steep gradient by maternal education is consistent with other studies [5][6][7][8][9][10] and is also in agreement with previous studies of birth weight, 13 infant mortality, 14 or child growth 15 in the Czech Republic. Maternal marital status, maternal age, and the number of previous live births (as a proxy for the number of children in a family) have all been previously found to strongly influence mortality from injuries in infants 5-8 10 and in young children.…”
Section: Consistency With Other Studiessupporting
confidence: 89%
“…There is evidence that in Western countries the rates of childhood injuries and accidents are more frequent in lower socioeconomic groups, 1 2 in families with marital discord, 3 and in areas with a higher level of deprivation. 4 Few studies have addressed this question in detail, and little research has focused on deaths in infancy.…”
mentioning
confidence: 99%
“…Others have also pointed to a correlation of family dysfunction with early childhood poisoning (Eriksson et al 1979;Husband & Hinton 1972 ;11-Iingworth 1974;Jones 1980;Rogers 1981;Sobel 1970;Sobel & Margolis 1965). Margolis (1971) performed a prospective follow-up study of 52 families of poisoned children 5 years later and found significant differences in their level of stress compared with that of control families.…”
Section: Social Isolation and Parenting Skillsmentioning
confidence: 94%
“…While it was previously assumed that drug overdoses were simply unavoidable accidents due to a lapse of parental supervision, previous research (Sobel & Margolis 1965) has discounted such randomness in favour of specific risk factors attributable to the host and their physical and social environment. Husband and Hinton (1972) suggested that children likely to experience a poisoning are more active than their peers and have negativistic personalities; they were more likely to be caught in power struggles with their parents.…”
Section: Repetitive Poisoning In Childrenmentioning
confidence: 97%
“…Again no consensus emerged. Previous studies (Husband and Hinton, ; Burn et al, ) have found that children who come from larger families are more likely to have an accident, whereas others found mixed (Manheimer et al ., ) or no effect. (Beautrais et al ., ).…”
Section: Introductionmentioning
confidence: 95%